Οι Σλάβοι στην Αθωνική μονή του Αγίου Παντελεήμονος - ΠΑΥΛΙΚΙΑΝΩΦ, Κύριλλος (Byzantina Symmeikta, 1999)
Cyril Pavlikianov The Slavs in the Athonite Monastery of Saint Panteleimon The article analyzes the prosopographical data concerning the presence of Slavs in the athonite monastery of Saint Panteleimon. The chronological frame of the survey extends from 998 to 1661. During the period 1262-1661 thirty-six monks of Slavic origin are identified. Thirteen of them (39.3%) appear as lingually neutral, three can be described as Russians (9%), seven use Bulgarian vernacular (21%), and seven seem to be Serbs (21%). It is obvious that the Russian-speaking monks prevailed during the earlier period, whereas the Serbs and the Bulgarians took their place after the middle of the 14th century. According to the evidence available, in 1395-1396 and 1469, the monastery of Saint Panteleimon had some contacts with the Bulgarian monasteries of Rila and Bačkovo. It is clear that in the 16th centuty the monastery was strongly influenced by the Serbs, so one may state that after the Turkish conquest the connection with the Russian lands was gradually lost in favour of the Balkan Slavs. However, Saint Panteleimon continued being perceived by the other athonite monks as a Russian monastery, even during the 17th century when the Turkish raids (1618) diminished its Slavic population.